A design of a short course with COTS UAV system for higher education students - Hong, Ju-Hyeon; Shin, Hyo-Sang; Tsourdos, Antonios (Elsevier, 2019)
This paper aims to propose a short course with a commercial off the shelf unmanned aerial vehicle (COTS UAV) system. From the short course, students can have a conception of a UAV system, and they would have not only the knowledge about the hardware integration but also the theoretical background of the guidance, navigation, and control (GNC) and the situation awareness system. The proposed course consists of two parts; the GNC system for holding the position and the situation awareness system with the marker detection and tracking. A Pixhawk is selected for a flight controller with an open source autopilot, i.e. px 4, and a Raspberry Pi with a downward camera is utilised for the visual navigation of the situation awareness system. The Pixhawk and Raspberry Pi are integrated into the robot operating system (ROS) via the WIFI network, and the MAVROS is adopted for the communication between the Pixhawk and the Raspberry Pi. The first part of the course is designed as the hands-on based lectures, and the second part of the course is adopted the problem-based project.
Keywords: UAV dynamics; control; guidance; navigation; Control algorithms implementation; Avionics; on-board equipment